SISTEM DISTRIBUSI BARANG ELEKTRONIK DENGAN METODE DISTRIBUSI LANGSUNG PADA TOKO MULIA - Aldy The; Sudirman; Hasniati (KHARISMA Tech, 2018)
This research aims to assist and improve the distribution process at Toko Mulia in managing data distribution and stock data items that produce reports in the form of detailed information distribution. The research stages are divided into seven stages, that is library study, field study, problem identification, data processing, system design, implementation, and system testing. System design include data modeling using ERD (Entity Relationship Diagram), then implemented using programming language Visual Basic 6.0 and Microsoft Access as database then system testing using black box testing method. The results of this research is the developed information system can manage the data distribution and ordering of electronic that can obtain important information from the resulting distribution report, so it can be used as a reference in determining the distribution strategy and the addition stock by Toko Mulia.